Effects of different amount of limb length discrepancy to vertical ground reaction force among the population with height of 150 and 170 cm - Saaid, Firdati Mohamed (2017)
Introduction: Leg length discrepancy is a known cause of gait asymmetry and can lead to subsequent changes in biomechanics of the lower limb. Although many studies have look into the significant amount of leg length discrepancy that causes problem to the limb biomechanics, none of them specified whether the amount is influenced by height of patients. We conducted this study to determine the effects of simulated leg length discrepancy on vertical ground reaction force in volunteers with different height. Methodology: This was a cross sectional study involving 14 volunteers with 150 cm height and 14 volunteers with 170 cm height. Vertical ground reaction force were measured using gait analysis study. Reflective markers were placed on bony landmarks of bilateral lower limbs to be captured by 3D motion cameras. Volunteers walked on a straight walkway with a force plate to measure ground reaction force. First measurement was taken without discrepancy as control. Subsequently leg length discrepancy simulated with shoe raise of 2, 3 and 4 cm and vertical ground reaction force were measured repeatedly on the longer leg. Measurement of first and second peak of vertical ground reaction force were taken for analysis separately. Vertical ground reaction force of simulated leg length discrepancy was compared with control. Repeated measures analysis of variance (ANOVA) within each groups’ height were done. Results: In both 150 and 170 cm height volunteers, the second peak of vertical ground reaction force in the longer leg reduced gradually when the shoe raise increased sequentially from 2 to 3 cm and then to 4 cm. Three cm discrepancy was statistically significant to cause reduction invertical ground reaction force on the longer limb with p-value of 0.001 and less in both group of volunteers (150 and 170cm height). Conclusions: Leg length discrepancy of 3 cm and above caused significant reduction in second peak ground reaction force. It was true for was both 150 and 170 cm height population. Reduction of ground reaction force in the longer leg can be inferred as increment of ground reaction force in the shorter leg, thus may indirectly cause problem in the joints of shorter leg.